Immune regulation: a new strategy for traditional Chinese medicine-based treatment of granulomatous lobular mastitis - Lou, Yuan; Xu, Han; Lu, Zixuan; Wang, Bin; Liu, Xiaofei (Frontiers in Immunology, 2024)
Granulomatous lobular mastitis (GLM) presents significant challenges, including high rates of morbidity, recurrence, and disability, ultimately impacting women's health and quality of life. Local autoimmune imbalance involving dysregulated cytokines and immune cells has been recognized to play a key role in the pathology of GLM.Traditional Chinese medicine (TCM), with its multi-component, multi-pathway and multi-target characteristics, offers unique advantages and broad prospects in the treatment of GLM. Here, we review the relationship between immune dysregulation and GLM, as well as the regulatory mechanisms of TCM-based interventions, with the aim of providing new insights and foundational knowledge for the clinical treatment of GLM, while promoting the further application and development of TCMbased strategies for the treatment of GLM.